The Effectiveness of proposed electronic course to develop cognitive awareness of cybersecurity among secondary school students in the city of Jeddah - Almatrafi, Bayan Bakheet; Alfarani, Leena Ahmad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the effectiveness of a proposed electronic course to develop the knowledge awareness of cybersecurity for female secondary school students in Jeddah, using the descriptive, analytical, and quasi-experimental approach. This is due to their relevance to the nature of the current study, and the study sample consisted of (26) female students who were deliberately chosen from the first-year secondary school students at the ninety-third secondary school in Jeddah. To achieve the objectives of the study, the two researchers applied the cybersecurity awareness test to the study sample before and after applying the proposed electronic course. The results showed that there were statistically significant differences at the significance level (α ≤ 0.05) between the mean scores of secondary school students in the pre and post application of the cyber security awareness test in favor of The post application is due to the proposed electronic course And the effectiveness of the electronic course in developing cognitive awareness of cybersecurity, as the total gain value reached (1.3), which is high earning rates if compared to the minimum for Black (1.2), which indicates the effectiveness of the proposed electronic course to develop knowledge awareness of cybersecurity for secondary school students in Jeddah. The study set a set of recommendations, the most important of which is to benefit from the proposed electronic course prepared by the two researchers as a course for cyber security for female secondary school students in Jeddah and other regions of the Kingdom of Saudi Arabia.
Keywords: electronic courses; cybersecurity; high school students